Factors Affecting Gut Microbiome in Daily Diet - Su, Qi; Liu, Qin (Frontiers in Nutrition, 2021)
There is a growing recognition that a good diet can help people maintain mental and physical health, while a bad one will cause the disorder of body function, and even lead to several diseases. A lot of attentions have been devoted to analyze every possible health-related factor in the daily diet, including food ingredients, additives and cooking process. With the support of high-throughput sequencing technology, there is accumulating evidence gradually clarifying that most of these factors are mainly through the interactions with gut microbiome to trigger downstream effects. The gut microbiome may be able to act as a very sensitive mirror in response to human daily diet. A complex network of interactions among diet, gut microbiome and health has been gradually depicted, but it is rarely discussed from a more comprehensive perspective. To this end, this review summarized the latest updates in diet-gut microbiome interactions, analyzed most identified factors involved in this process, showed the possibility of maintaining health or alleviating diseases by diet intervention, aiming to help people choose a suitable recipe more accurately.